A simple and cost effective method for determination of the self‐accelerating decomposition temperature. Issue 2 (24th April 2013) - Fauske, Hans K.
<x xml:space="preserve">Abstract</x> This article describes a simple cost effective alternative to the United Nations tests for determining the Self Accelerating Decomposition Temperature (SADT) for transporting reactive chemicals. The proposed method uses simple calorimetry results together with well known heat loss models. Some detailed results and analysis are included that show (a) the proposed method gives essentially identical results as the United Nations H.1, H.2, and H.3 results, (b) the proposed method is not sensitive to the shape of the reactant, and (c) the proposed method can be easily used to determine results as a function of various conditions. This alternative method provides correct SADT of the substance as packaged for transport, and is, therefore, consistent with suggestions by the United Nations "Recommendation on the Transport of Dangerous Goods." © 2013 American Institute of Chemical Engineers Process Saf Prog, 2013